Calderón–Lozanovskii Construction for a Couple of Global Morrey Spaces - Berezhnoi, Evgenii (Eurasian Mathematical Journal, 2023)
It is shown that under certain conditions on the parameters included in the definition of global Morrey spaces, the Calderón–Lozanovskii construction on a pair of global Morrey spaces gives a space of the same type. Calculation of the Calderón–Lozanovskii construction for a pair of global Morrey spaces allowed us to obtain new interpolation theorems even for classical global Morrey spaces.